Pediatric head and neck rhabdomyosarcoma: An analysis of treatment and survival in the United States (1975–2016). (December 2020) - Darwish, Christina; Shim, Timothy; Sparks, Andrew D.; Chillakuru, Yeshwant; Strum, David; Benito, Daniel A.; Monfared, Ashkan
Abstract: Introduction: Rhabdomyosarcoma (RMS) is the most common soft tissue head and neck sarcoma in children. Stringent analysis of survival data is imperative to optimize treatment. Methods: The National Cancer Database (NCDB, 2004–2016) and the Surveillance, Epidemiology, and End Results Program (SEER, 1975–2016) were queried for patients ages 0–19 with RMS of the head and neck. Survival trends were analyzed using univariable logistic regression and Chi-square pairwise comparisons. Survival by treatment was analyzed using log-rank tests, Kaplan Meier, and multivariable Cox-proportional hazards regression. Results: 1147 (63.3% age <10 years, 54.3% male) and 459 (71.4% age <10 years, 53.6% male) patients were identified in NCDB and SEER, respectively. In NCDB, embryonal (n = 625, 54.5%) and alveolar (n = 300, 26.2%) were the most common histology and nonparameningeal/non-orbital (n = 634, 55.3%), followed by parameningeal (n = 303, 26.4%) and orbital (n = 210, 18.3%) the most common location. Five-year overall survival (OS) was 70.3% with lower mortality risk for embryonal histology (adjusted HR [aHR] = 0.69, p = 0.0038). Orbital tumors had greatest survival (5-year OS = 92.4%) of all sites, and their mortality risk was higher with chemotherapy and radiation compared to surgery and radiation (aHR = 6.27, p = 0.0302). SEER analysis showed average increased survival by 4% per year (p < 0.0001), but no significant 5-year OS difference when comparing 1976–1980 and 2006–2010 (p = 0.0843). Conclusions: Major prognostic factors for survival in childhood RMS of the head and neck were embryonal histology, orbital site, extent of disease, and use of SRT for orbital tumors. Larger population studies are required to demonstrate survival differences between treatment modalities for other sites.